Evaluation of Neoadjuvant Chemotherapy Effects on Liver Parenchyma in Resected Pediatric Malignancies. (1st August 2013) - Grazia Scuderi, Maria; Magro, Gaetano; Cataldo, Andrea Di; Pesce, Antonino; Scalora, Luisa; Vecchio, Giada Maria; Portale, Rosanna; Benedetto, Vincenzo Di; Puleo, Stefano
Abstract : Neoadjuvant chemotherapy for colorectal liver metastases in adults is responsible for chemotherapy-associated liver injury (CALI), characterized by steatosis, steatohepatitis, and sinusoidal obstruction syndrome. These alterations cause delayed operation to reduce the risk of hemorrhage, portal hypertension, and hepatic failure. Children with hepatic malignancies usually receive neoadjuvant chemotherapy prior to surgery. The aim of this study was to evaluate retrospectively whether the CALI occurs in this pediatric population. This study evaluated patients referred since 1996 for hepatic malignancies who received hepatectomy after chemotherapy. Liver resection material was reviewed, in order to investigate the presence of morphological changes compatible with the CALI in the peritumoral hepatic tissue. Twelve patients were recruited. All patients satisfied the inclusion criteria except one who did not receive neoadjuvant chemotherapy. Eleven children underwent surgery 1 month after the last chemotherapy cycle. All are alive disease-free. Histological examination of specimen revealed only mild changes such as diffuse swelling of hepatocytes and focal, mild portal inflammation. Severe hepatic changes such as steatosis, necrosis, or fibrosis were not identified. CALI-related morphological changes were not found in our patients. The absence of the CALI could be attributed to the younger age of patients (possible different response to stress) and/or to the different chemotherapy schedules compared to those in use for adults patients.